GENERALISED ANALYSIS OF A DYNAMIC SYSTEM FOR THE PRESENCE OF SIGNS OF THE JORDAN FORM - R.A. NEYDORF; N.H. PHAN (Advanced Engineering Research)
An efficient analytical method of studying multidimensional systems with a purpose of extracting controllable sub-systems of the Jordan forms is presented. A mathematical model and algorithms for estimation of the presence of Jordan signs in controllable multidimensional systems on the basis of which a decomposition of these multidimensional systems into Jordan sub-systems has been built.